Evaluation of Alpha-Amylase Inhibitory, Antioxidant, and Antimicrobial Potential and Phytochemical Contents of Polygonum hydropiper L. - Abdul Nasir; Mushtaq Khan; Zainab Rehman; Atif Ali Khan Khalil; Saira Farman; Naeema Begum; Muhammad Irfan; Wasim Sajjad; Zahida Parveen (Plants, 2020)
Polygonum hydropiper L. is a traditionally used medicinal plant. The present study was designed to explore the α-amylase inhibitory, antioxidant, and antimicrobial activities of Polygonum hydropiper L. Polarity-based solvent extracts (n-hexane, acetone, chloroform, methanol, ethanol, and water) of Polygonum hydropiper leaves and stem were used. Antioxidant activity was assessed by free radical scavenging assay (FRAP) and 2,2-diphenylpicrylhydrazyl (DPPH) free radical scavenging activity methods. Quantitative phytochemical analyses suggested that the stem of Polygonum hydropiper L. contains higher levels of bioactive compounds than its leaves (p < 0.05). The results suggested that stem-derived extracts of Polygonum hydropiper L. are more active against bacterial species, including two Gram-positive and three Gram-negative strains. Moreover, our results showed that the bioactive compounds of Polygonum hydropiper L. significantly inhibit α-amylase activity. Finally, we reported the polarity-based solvent extracts of Polygonum hydropiper L. and revealed that the stem, rather than leaves, has a high antioxidant potential as measured by FRAP and DPPH assay with IC50 values of 1.38 and 1.59 mg/mL, respectively. It may also be deducted from the data that the Polygonum hydropiper L. could be a significant candidate, which should be subjected to further isolation and characterization, to be used as an antidiabetic, antimicrobial and antioxidant resource in many industries, like food, pharmaceuticals and cosmetics.